APPLICATION BASED LEARNING : THE USE OF ROSETTA STONE IN STUDENT’S ENGLISH PRONUNCIATION - Yana, Riska Sofi; Suryawati, Sri Suci; Zakiyah, Zakiyah (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
The objective of this study was to investigate the effect of using the Rosetta Stone application on the English pronunciation skills of eleventh-grade vocational high school students. Pronunciation is a crucial component of communication, as mispronunciation can cause misunderstandings and reduce the effectiveness of interaction. Therefore, effective learning media are needed to help students improve their speaking ability and boost their confidence. This study employed a quantitative approach with a quasi-experimental non-equivalent control group design, involving 36 students in the experimental class and 35 students in the control class. Data were collected through pre-tests and post-tests to measure students’ pronunciation performance. The pre-test mean score of the experimental class was 61.51 (SD = 2.3), while the control class had a mean of 60.5 (SD = 1.76). After the treatment, the post-test mean score of the experimental class increased to 75.31 (SD = 6.19), with scores ranging from 61.5 to 84.5, whereas the control class reached 66.27 (SD = 3.39), with scores ranging from 61.5 to 75.31. Finding emphasizes that the Rosetta Stone application provides technology-based interactive exercises that can improve students’ articulation, word stress, intonation, and fluency. These results indicate that the application is an effective tool to support pronunciation learning in EFL classes, helping students speak more confidently and communicate more clearly and naturally in English ABSTRAKTujuan dari penelitian ini adalah untuk menyelidiki pengaruh penggunaan aplikasi Rosetta Stone terhadap keterampilan pelafalan bahasa Inggris siswa kelas XI SMK. Pelafalan merupakan komponen penting dalam komunikasi, karena kesalahan pengucapan dapat menyebabkan kesalahpahaman dan mengurangi efektivitas interaksi. Oleh karena itu, diperlukan media pembelajaran yang efektif untuk membantu siswa meningkatkan kemampuan berbicara dan membangun kepercayaan diri. Penelitian ini menggunakan pendekatan kuantitatif dengan desain kuasi-eksperimen non-equivalent control group, yang melibatkan 36 siswa pada kelas eksperimen dan 35 siswa pada kelas kontrol. Data dikumpulkan melalui pre-test dan post-test untuk mengukur performa pelafalan siswa. Nilai rata-rata pre-test kelas eksperimen adalah 61,51 (SD = 2,3), sedangkan kelas kontrol memiliki rata-rata 60,5 (SD = 1,76). Setelah perlakuan, nilai rata-rata post-test kelas eksperimen meningkat menjadi 75,31 (SD = 6,19), dengan skor terendah 61,5 dan tertinggi 84,5, sementara kelas kontrol mencapai 66,27 (SD = 3,39), dengan skor terendah 61,5 dan tertinggi 75,31. Temuan menekankan bahwa aplikasi Rosetta Stone menyediakan latihan interaktif berbasis teknologi yang dapat meningkatkan artikulasi, penekanan kata, intonasi, dan kelancaran siswa. Hasil ini menunjukkan bahwa aplikasi tersebut merupakan alat yang efektif untuk mendukung pembelajaran pelafalan dalam kelas EFL, membantu siswa berbicara dengan lebih percaya diri serta berkomunikasi dengan lebih jelas dan natural dalam bahasa Inggris.